Scrotal calculi with delayed urethroscrotal fistula: a rare case presentation with literature review - Aggarwal, Ramesh K. (International Surgery Journal, 2019)
Scrotal calculi are not so common entity in the clinical presentation. Scrotourethral fistula is an abnormal communication between scrotal skin and the urethra, usually result of the inflammation and due to perforation by urethral calculi and sometimes iatrogenic due to surgery done for urethral stone removal or uretheroplasty. We present here a very rare case of young adult gentleman who initially presented with a scrotal swelling, turned out into scrotal calculi while doing surgical excision, later on presented as uretheroscrotal fistula that managed conservatively. After going through the available literature and through the pub med articles (approx 148 articles while searching with titles of ‘scrotal calculi’, ‘scrotourethral fistula’, ‘uretherocutaneous fistula’) we found only 1-2 cases of scrotourethral fistula. A high index of clinical suspicion and examination is needed to diagnose such asymptomatic rare presentation cases.